Yata Virus (Family Rhabdoviridae, Genus Ephemerovirus) Isolation from Mosquitoes from Uganda, the First Reported Isolation since 1969 - Lara C. Perinet; John-Paul Mutebi; Ann M. Powers; Julius J. Lutwama; Eric C. Mossel (Diseases, 2023)
As a part of a systematic study of mosquitoes and associated viruses in Uganda, a virus was isolated from a pool of Mansonia uniformis collected in July 2017, in the Kitgum District of northern Uganda. Sequence analysis determined that the virus is Yata virus (YATAV; Ephemerovirus yata; family Rhabdoviridae). The only previous reported isolation of YATAV was in 1969 in Birao, Central African Republic, also from Ma. uniformis mosquitoes. The current sequence is over 99% identical at the nucleotide level to the original isolate, indicating a high level of YATAV genomic stability.